KANCHNAR GUGGULU AND VARUNADI KASHAYA IN HYPOTHYROIDISM - A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2015)
Thyroid is one of the earliest endocrine glands to build up. After diabetes thyroid is the second most prevailing disorder in daily OPD. The thyroid gland secretes two hormones, tetraiodothyronine or thyroxine (T4) and triiodothyronine (T3). The most common presentation of thyroid disease are thyrotoxicosis (graves disease) i.e., hyper functioning of thyroid gland, hypo thyroidism, (creatinisim) in children, myxoedema in females and enlargement of gland called as goiter. Iodine (I) is the trace element required for thyroid hormone synthesis, In hypo thyroidism TSH level is increased, where as in hyper thyroidism TSH level is decreased, both the conditions exhibit different signs and symptoms. The prevalence of primary hypothyroidism is1:100, but increases to 5:100. The female-male ratio is approximately 6:1. In modern science, the treatment of hypothyroidism is done by Thyroxine therapy for lifelong starting from 25mcg/day.There is no direct reference of thyroid in Ayurvedic classics, where as the Galganda and Gandmala have been frequently used in the text. According to Charaka presentation of multiple Granthi around the neck is called Gandmala and single swelling on the Parshav of the neck is Galgand. Galgand is explained classically in all the Ayurvedic texts, including Shushruta and Astang hruday,since Galgand is the most untouched topic in Ayurveda and since thyroid is becoming one of the common problems in day-to-day practice.However in recent times it has been observed that thyroid can be very well managed with Ayurvedic drugs, although modern drugs are quite effective in getting TSH level down but with certain side effects. So a case of hypothyroidism was selected and observed before and after the treatment.Kanchnar is considered as a drug of choice for Granthi vikar and Galgand, so here in this case Kanchnar guggulu along with Varunadi kashaya along with Trivrit avleha was administered for the purpose of Nitya virechana. The patient was followed upto 6months to observe increase in value of TSH.